Does Gastronomy Tourism Experiences Matter? Understanding Malang's Domestic Tourist Future Behavior - Prasetyo, Bambang Dwi; Pramesthi, Hanum Kanthi; Muchtar, Moch. Shobastian Mahendra (Jurnal Ilmu Sosial dan Humaniora, 2024)
This research seeks to examine how gastronomic tourism, particularly through Bakso, affects tourist satisfaction, intention to return, and recommendations to others in Malang City. The study employs Partial Least Squares Structural Equation Modeling (PLS SEM) and includes a sample of 109 respondents. Data was collected via questionnaires distributed in January 2024. PLS SEM helps identify three key variables: Gastronomy Tourism Experience, Tourist Satisfaction, and Future Behavior, represented by 37 questionnaire items. Findings indicate that Bakso-based gastronomic tourism significantly enhances tourist satisfaction, their likelihood of returning, and their propensity to recommend Malang City. This underscores the strategic importance of local food culture in tourism development and suggests that local governments should prioritize enhancing the tourist experience and food tourism infrastructure. The study lays the groundwork for further exploration of Malang City's gastronomic tourism potential.